Men stepping forward : leading your organisation on the path to inclusion - Kelan, Elisabeth (Bristol University Press, 2023)
How do men interested in gender equality become 'change makers' and lead their organisation towards inclusion? Directly addressing men, this innovative book reveals how they can be centrally involved in creating gender-inclusive cultures in their organisations. Using cutting-edge research, it suggests practical actions for men as leaders and managers to implement in order to make real changes . Ideal for the time-poor professional, it is essential reading for all men who want to make a difference but don't know where to start.